Whole-exome analysis of foetal autopsy tissue reveals a frameshift mutation in OBSL1, consistent with a diagnosis of 3-M Syndrome. (December 2015) - Marshall, Christian; Farrell, Sandra; Cushing, Donna; Paton, Tara; Stockley, Tracy; Stavropoulos, Dimitri; Ray, Peter; Szego, Michael; Lau, Lynette; Pereira, Sergio; Cohn, Ronald; Wintle, Richard; et al.
Abstract Background We report a consanguineous couple that has experienced three consecutive pregnancy losses following the foetal ultrasound finding of short limbs. Post-termination examination revealed no skeletal dysplasia, but some subtle proximal limb shortening in two foetuses, and a spectrum of mildly dysmorphic features. Karyotype was normal in all three foetuses (46, XX) and comparative genomic hybridization microarray analysis detected no pathogenic copy number variants. Results Whole-exome sequencing and genome-wide homozygosity mapping revealed a previously reported frameshift mutation in theOBSL1 gene (c.1273insA p.T425nfsX40), consistent with a diagnosis of 3-M Syndrome 2 (OMIM #612921), which had not been anticipated from the clinical findings. Conclusions Our study provides novel insight into the early clinical manifestations of this form of 3-M syndrome, and demonstrates the utility of whole exome sequencing as a tool for prenatal diagnosis in particular when there is a family history suggestive of a recurrent set of clinical symptoms.